Design and Validation of the Scientific-Research Skills Questionnaire for Basic Education Teachers - Gilber Chura-Quispe; Bianca Daisa Laura-De-La-Cruz; Patricia Rosa María Nué Caballero; Edith Cristina Salamanca Chura; Héctor Octavio Guido Torres Orihuela (Qubahan Academic Journal)
One teacher skill that has allowed for progress and development in pedagogy is that of scientific research, but there is very little attention to its measurement in basic education. The aim of the study was to design and validate a questionnaire of teachers' scientific-research skills and to compare them according to socio-demographic variables. The design was psychometric and descriptive-comparative with the participation of 736 Peruvian teachers. The results indicate that the instrument has evidence of content validity with a concordance > 0.7 among the 9 judges. The exploratory factor analysis (EFA) exposed 25 items and 3 dimensions that explained 81.1% of the total variance (KMO > 0.7, Bartlett < 0.05) and was confirmed by adequate fit indices (X2/df = 4.648, p < 0.001, SRMR=0.036, RMSEA=0.099, TLI, CFI and GFI >0.95). The values obtained for convergent validity (AVE > 0.5), discriminant validity (√AVE > r) and internal consistency (αordinal and ωordinal > 0.7) exceeded the minimum expected values. In addition, it was found that there are moderate and significant differences in the skills of problematisation and research theorisation, research contrastation and scientific communication according to teaching levels in favour of secondary school teachers and in academic training with higher scores in teachers with a doctorate degree (p < 0.05; ɛ̂ > 0.25). In conclusion, the questionnaire has adequate evidence of validity and reliability, and there are differences in teachers' abilities according to teaching and training levels.